Leverage, Investment Account Holder (IAH), Frekuensi Rapat Dewan Pengawas Syariah, Frekuensi Rapat Dewan Komisaris, Frekuensi Rapat Komite Audit Dan Pengaruhnya Terhadap Pengungkapan Akuntabilitas - Najah, Hasna Afifatun; Mukhibad, Hasan (AKTSAR: Jurnal Akuntansi Syariah, 2022)
This study aimed to determine the effect of Leverage, investment account holders, the frequency of sharia supervisory board meetings, the frequency of board of commissioners meetings, and the frequency of audit committee meetings on accountability disclosure (financial, social, sharia). The object of this research is 14 Islamic commercial banks in Indonesia. The sampling technique was purposive sampling, so 108 units of analysis were obtained. The data was analyzed by panel data regression analysis in the form of a fixed effect model (FEM). The results of this study indicate that investment account holders, the frequency of sharia supervisory board meetings, and the frequency of audit committee meetings have a positive effect on accountability disclosure. However, Leverage and the frequency of board of commissioners' meetings have no impact on accountability disclosure.